Macromol. Chem. Phys. 24/2014. Issue 24 (December 2014) - Nöchel, Ulrich; Kumar, Uttamchand Narendra; Wang, Ke; Kratz, Karl; Behl, Marc; Lendlein, Andreas; Lendlein, Andreas; Behl, Marc
<x xml:space="preserve">Abstract</x> Front Cover: A specimen of a triple shape‐memory polymer subsequently recovers two memorized shapes. The sequence of shape changes occurring at both ends is determined by the corresponding switching temperatures, which are tunable. The spherical inset represents the anisotropic wide‐angle X‐ray scattering (WAXS) pattern of the temporary shape (left), and an isotropic pattern is presented when the permanent shape is recovered (right). Further details can be found in the article by U. Nöchel, U. N. Kumar, K. Wang, K. Kratz, M. Behl, and A. Lendlein* on page 2446. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>